On the Design of Circular Fractal Antenna with U-Shape Slot in CPW-Feed - Kumar, Raj (Scientific Research Publishing, 2010)
new ultawideband circular fractal antenna with notched-band characteristics is presented. A notched-band characteristic is achieved by employing a U-shape slot in 50 Ω feed lines. The ultra-wideband impedance matching and compact size have been obtained by using CPW-feed technique and the fractal concept. The measured result of proposed fractal antenna exhibits the ultra wideband characteristics from 3.0 to 18.0 GHz at VSWR 2:1 except notched-band frequency. The proposed antenna has been analyzed theoretically and experimentally with respect to design parameters. The measured radiation pattern of fractal antenna is nearly omnidirectional in azimuth plane throughout the operating frequency. This antenna is useful for UBW communication system.
Keywords: Monopole Antenna; Wideband Antenna; Resonant Frequency; Fractal Antennas; Multib; Antenna